Absorption-improving effects of chitosan oligomers based on their mucoadhesive properties: a comparative study on the oral and pulmonary delivery of calcitonin. (1st September 2016) - Zhang, Hailong; Huang, Xiaoyan; Sun, Ya; Xing, Jianfeng; Yamamoto, Akira; Gao, Yang
Abstract: Effects of chitosan oligomers with different types and varying concentrations on the intestinal and pulmonary absorptions of calcitonin were investigated in rats by an in situ closed loop method and an in vivo pulmonary absorption experiment, respectively. Various chitosan oligomers demonstrated different efficiencies in improving the intestinal and pulmonary absorptions of calcitonin, and chitosan hexamer with the optimal concentration of 0.5% (w/v) showed the greatest absorption enhancing effect. Moreover, pharmacodynamic parameters of calcitonin after its coadministration intrapulmonarily with various chitosan oligomers were consistently larger than that in the intestinal delivery, indicating the superior potential of pulmonary administration for systemic delivery of calcitonin. Furthermore, various chitosan oligomers neither obviously increased release amounts of protein nor activities of lactate dehydrogenase (LDH) in bronchoalveolar lavage fluid (BALF), revealing the safety of these chitosan oligomers to lung tissue. In addition, bioadhesions of various chitosan oligomers were well consistent with their absorption enhancing effects in the absorption experiment, suggesting the contribution of mucoadhesive properties of chitosan oligomers to their absorption improving effects. Taken together, chitosan oligomers, especially chitosan hexamer, can effectively improve the intestinal and pulmonary absorptions of calcitonin partly due to the mucoadhesion between positive chitosan oligomers and negative mucus in the membrane.